CROSS-BORDER MARRIAGE MIGRATION OF VIETNAMESE WOMEN TO CHINA - Su, Lianling (Kansas State University, 2013)
This study analyzes the cross-border marriage migration of Vietnamese women to China. It is based on sixty-four in-depth interviews with Chinese-Vietnamese couples living in Guangxi province, near the border between China and Vietnam. Most of these Vietnamese women are “invisible,” or undocumented, in China because they do not have legal resident status. The women came from rural areas in northern Vietnam and generally have relatively lower levels of education. The primary reason the Vietnamese women chose to marry Chinese men rather than Vietnamese men was to have a better life in China; the women stated that living in China was better because of its stronger economic conditions, higher standard of living, and the higher quality of housing for families. Many of the Vietnamese women stated that by marrying Chinese men, they could also support their family in Vietnam. The Chinese men who marry Vietnamese women tend to be at the lower end of the social-economic spectrum with limited education. These men often have difficulties finding Chinese wives due to their low economic status and the overall shortage of local Chinese women. Both the Vietnamese women and Chinese men use different types of informal social networks to find their potential spouses. The cultural (particularly linguistic) similarities and historical connections between the border regions of China and Vietnam facilitate cross-border marriages and migration, which are likely to continue in the future.
Keywords: Marriage Migration; Geography (0366)